Development of Framework for Data and Evidence Collection in Root Cause Analysis for Petrochemical Plant - Sulaiman, Mohammad Syafiq (IRC, 2017)
Root Cause Analysis (RCA) is an analysis procedure executed in order to search for root causes when there are failure occur. Which in turn, Root Causes Analysis are expected to assist one to come out with proper recommendation and thus avoid from same failure happening. However, in petrochemical plant RCA investigation, the data and evidence collection process have been said to be ineffective and lack of effectiveness. Therefore, the data and evidence collection process in RCA for petrochemical plant application should be further develop to increase their effectiveness. This study objective is to develop data and evidence collection framework for comprehensive data and evidence gathering process for application in petrochemical plant RCA investigation. To achieve this, a comparative study of five selected investigation method was carried out to determine the best practices in data and evidence collection process. Based on the comparative study findings, the data and evidence collection framework has been develop. The framework generated outlined five (5) main component for the data and evidence to be collected. The components outlined are recorded data and evidence, physical evidence, photographical data and evidence, diagrams or sketches, and lastly testimony with each components have their sub-component of the type of data and evidence. After the framework has been develop, a case study was carried out to verify and demonstrate the process of data and evidence collection process using the framework generated. The case study show that the framework generated in this study are practical and therefore can be used as a guideline for RCA investigators during the data and evidence collection phase for their investigation.